2022
DOI: 10.3390/catal12040374
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Catalysis for Methanation of CO2 from Biogas

Abstract: Biogas, with its high carbon dioxide content (30–50 vol%), is an attractive feed for catalytic methanation with green hydrogen, and is suitable for establishing a closed carbon cycle with methane as energy carrier. The most important questions for direct biogas methanation are how the high methane content influences the methanation reaction and overall efficiency on one hand, and to what extent the methanation catalysts can be made more resistant to various sulfur-containing compounds in biogas on the other ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 95 publications
0
11
0
Order By: Relevance
“…The conversion of CO 2 into hydrocarbons via hydrogenation is a promising method of making waste into valueadded materials. [10,[264][265][266][267][268][269][270][271][272][273] This reaction can solve the environmental and energy issues caused due to CO 2 emissions. Hydrogenation of CO 2 can be used to synthesize valuable compounds: (1) hydrocarbons, such as methane (CH 4 , the reaction can be called methanation), [270,274] olefins, and gasoline, or (2) other compounds, such as formic acid (HCOOH), alcohol (e.g., methanol), and carbon monoxide (CO).…”
Section: Hydrogenation For Comentioning
confidence: 99%
See 1 more Smart Citation
“…The conversion of CO 2 into hydrocarbons via hydrogenation is a promising method of making waste into valueadded materials. [10,[264][265][266][267][268][269][270][271][272][273] This reaction can solve the environmental and energy issues caused due to CO 2 emissions. Hydrogenation of CO 2 can be used to synthesize valuable compounds: (1) hydrocarbons, such as methane (CH 4 , the reaction can be called methanation), [270,274] olefins, and gasoline, or (2) other compounds, such as formic acid (HCOOH), alcohol (e.g., methanol), and carbon monoxide (CO).…”
Section: Hydrogenation For Comentioning
confidence: 99%
“…Hydrogenation of CO 2 can be used to synthesize valuable compounds: (1) hydrocarbons, such as methane (CH 4 , the reaction can be called methanation), [270,274] olefins, and gasoline, or (2) other compounds, such as formic acid (HCOOH), alcohol (e.g., methanol), and carbon monoxide (CO). [10,[264][265][266][267][268][269][270][271][272][273] Hydrogenation can be promoted via electrochemical, [275] thermo-catalysis, [276] and photo/thermal [277] methods. ZIF materials are promising catalysts in terms of efficiency and selectivity among several catalysts.…”
Section: Hydrogenation For Comentioning
confidence: 99%
“…The conversion of CO2 into hydrocarbons via hydrogenation is a promising method of making waste into value-added materials [10,[261][262][263][264][265][266][267][268][269][270] . This reaction can solve the environmental and energy issues caused due to CO2 emissions.…”
Section: Hydrogenation For Co2mentioning
confidence: 99%
“…This reaction can solve the environmental and energy issues caused due to CO2 emissions. Hydrogenation of CO2 can be used to synthesize valuable compounds; 1) hydrocarbons, such as methane (CH4, the reaction can be called methanation) [267,271] , olefins, and gasoline, or 2) other compounds, such as formic acid (HCOOH), alcohol (e.g., methanol), and carbon monoxide (CO) [10,[261][262][263][264][265][266][267][268][269][270] . Hydrogenation can be promoted via electrochemical [272] , thermo-catalysis [273] , and photo/thermal [274] methods.…”
Section: Hydrogenation For Co2mentioning
confidence: 99%
“…This research also showed that the introduction of H 2 S traces along with the feed stream led to a fast drop in CO 2 conversion and CH 4 selectivity. The presence of CH 4 and H 2 S clearly affects the activity of methanation catalysts, but this influence depends on the catalyst composition and reactions conditions [39]. A pilot-scale experimental setup highlighted the importance of controlling the exothermicity of the Sabatier reaction [9,40].…”
Section: Introductionmentioning
confidence: 99%